Social representations of artistic practices in rural schools - Cristiene Adriana da Silva Carvalho (Revista Brasileira de Educação do Campo, 2021)
This work analyzes the movement of re-elaboration of social representations on artistic practices of rural teachers. These educators have graduated Rural Education from Faculdade de Educação at Universidade Federal de Minas Gerais, Brazil. Artistic practices constitute a way of creation, fruition, and reflection of art present in education processes. Those practices carry historicity and resistance embedded in the struggle of social movements to the right of rural education. The theoretical background is guided by the Social Representations in Movement, related to the Theory of Social Representations. The methodological approach is based on narrative interviews and observations of pedagogical practices. The data analysis was built from the reconstruction of trajectories considering the movement of the Social Representations. We have observed that the artistic practices can be seen as a pedagogical mechanism of the struggle for transforming education and by strengthening rural identities.